The Effect of â€œSELF-HELP Packagesâ€ on Post Stroke Depression among Ischemic Stroke Survivors - Handayani, Fitria; Setyowati, Setyowati; Pudjonarko, Dwi; Sawitri, Dian Ratna (Department of Nursing, Faculty of Medicine, Diponegoro University, 2020)
Background: There are several factors that contribute to Post Stroke Depression (PSD). Since a single intervention is proven ineffective to deal with PSD, an intervention which includes biological, psychological, social, and spiritual aspects (â€œSELF-HELP Packagesâ€), therefore, needs to be established.Purpose: The purpose of the study was to investigate the effect of â€œSELF HELP Packagesâ€ intervention on PSD among ischemic stroke survivors after three months from onset and its effect after confounding variables were controlled.Methods: This study was a pre and post quasi-experiment with a control group involving 34 ischemic stroke survivors each group. The inclusion criteria were survivors after three months from ischemic stroke, no aphasia, having a good hearing, and having Mini Mental Status Examination (MMSE) score of â‰¥ 22. GRID-HAMD 17, Multidimensional Scale of Perceived Social Support (MSPSS), and Barthel-Index were used to measure PSD, social support, and functional status respectively. â€œSELF-HELP Packagesâ€ intervention was delivered in three sessions, namely information delivery, discussion and activity. Statistical analyses were conducted using McNemar test, Chi-square and logistic regression.Results: The result showed that â€œSELF-HELP Packagesâ€ considerably decreased PSD in the intervention group (p=0.004). There were also significant differences in PSD after the intervention between two groups (p=0.008). Logistic regression showed that â€˜SELF-HELP Packageâ€ had no effect on PSD when other confounding variables were controlled (p=0.075, OR=0.288, 95% CI 0.073 â€“ 1.135).Conclusion: SELF-HELP Packagesâ€ should be applied in providing the nursing intervention among stroke ischemic survivors in clinical setting. A longer period of time for the intervention is also recommended for the next study in order to obtain a more robust result.Â Â Â